Maturation of pluripotent stem cell-derived cardiomyocytes: limitations and challenges from metabolic aspects - Xi Jiang; Xin Lian; Kun Wei; Jie Zhang; Kaihua Yu; Haoming Li; Haichun Ma; Yin Cai; Lei Pang (Stem Cell Research & Therapy, 2024)
Abstract Acute coronary syndromes, such as myocardial infarction (MI), lack effective therapies beyond heart transplantation, which is often hindered by donor scarcity and postoperative complications. Human induced pluripotent stem cells (hiPSCs) offer the possibility of myocardial regeneration by differentiating into cardiomyocytes. However, hiPSC-derived cardiomyocytes (hiPSC-cardiomyocytes) exhibit fetal-like calcium flux and energy metabolism, which inhibits their engraftment. Several strategies have been explored to improve the therapeutic efficacy of hiPSC-cardiomyocytes, such as selectively enhancing energy substrate utilization and improving the transplantation environment. In this review, we have discussed the impact of altered mitochondrial biogenesis and metabolic switching on the maturation of hiPSC-cardiomyocytes. Additionally, we have discussed the limitations inherent in current methodologies for assessing metabolism in hiPSC-cardiomyocytes, and the challenges in achieving sufficient metabolic flexibility akin to that in the healthy adult heart.